HUBUNGAN RIWAYAT KERJA TERHADAP PENGETAHUAN VALIDASI DAN KUALIFIKASI BERDASARKAN CPOTB DI USAHA KECIL OBAT TRADISIONAL PT. X di DAERAH ISTIMEWA YOGYAKARTA - Banafsaj, Zakia Irbah; Dwinta, Eliza; Emelda, Emelda; Sarwadhamana, Raden Jaka (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2023)
Validation and qualification are important activities the pharmaceutical industry to produce quality and safe drugs. Good Manufacturing Practices for Traditional Medicines (CPOTB) is a guideline for the traditional medicine industry to produce medicines with guaranteed quality from validation and qualifications. Employee knowledge in carrying out validation and qualifications in the traditional medicine industry is very necessary to support the production quality assurance process. The aim of the research is to determine the relationship between work history (length of work and work area) on validation knowledge and qualifications based on CPOTB in the small business of traditional medicine PT. X in the Special Region of Yogyakarta. The type of research is descriptive quantitative with a cross sectional method. The research uses primary data from questionnaires of 35 employees who work in the production sector of PT. X. The results showed that there was no work history relationship with employee knowledge of CPOTB, with a p-value of 0.496 (<0.05) in the length of work and a p-value of 0.724 (<0.05) in the work area. From the data it can be concluded that the length of work and employee work area in the production sector are not related to employee knowledge of CPOTB.